Development of Web and Mobile based Inventory Information System in Transitco Companies - Soleh Sabarudin (NUANSA INFORMATIKA, 2020)
Currently the system that is running still has many shortcomings and weaknesses causing the company's performance to be hampered and has not been able to support all the needs that the company wants such as the report preparation that is long enough so that the owner waits long to get it. This study aims to analyze and design a web-based inventory system that can present the information needed. Operations that run on this system are: check goods, input sales data, input purchase data, convection data input, purchase reports, and sales reports. The use of this system is divided into two accesses, namely for employees and owners so that they can easily manage goods data. The development tools used in this study use the CI, PHP framework as a programming language and phpMyAdmin 4.7.9 as the MySQL DBMS interface. Design and design an inventory system for TransitCo Bandung goods using the Unified Modeling Language (UML) method as its modeling tool. This Inventory system is web and mobile based so it is more dynamic and can be used easily and user friendly. The system is used to manage goods data with various menus available both for employees and the owner.Keywords: Unified Modeling Language (UML), PHP and MySQL, Inventory